INFLUENCE OF CERTAIN TRAITS AS RESISTANCE INDUCING FACTORS AGAINST SHOOT FLY (Atherigona soccata therigona soccata) AND STEM BORER ( BORER (Chilo partellus Chilo partellus) IN LEADING MAIZE ( ) IN LEADING MAIZE (Zea mays Zea mays Zea mays L) GENOTYPES - KHAWAR JAWAD AHMED; QURBAN ALI; RAJENDRA KUMAR SINGH; RIAZ AHMED; IMRAN NADEEM; M. FAHEEM AKHTAR (The Bioscan, 2018)
The alarming population growth rate in Pakistan has exacerbated the food security problem. Maize which is important source of dietary protein is the highest yield cereal crop in the world. The use of crop varieties resistant or tolerant to insect pests stress is an imperative approach in non-chemical crop protection. In the presented study, 9 genotypes of Maize hybrid/advanced lines i.e., FH-793, FH-810, FH-949, NK-8711, P15- M43, FH-985, FH-988, FH-1036 and FH-1046 were screened out against insect pests during 2016. Minimum shoot fly percentage infestation (5.87%) was recorded on FH-810 while maximum (21.46%) on FH-1046. Minimum stem borer % damage was recorded in FH-810 (1.32%) while maximum (8.23%) on FH-1046. During this study physiomorphic characters (Plant height (cm), stem diameter (cm), leaf hair density (cm2 ) and chlorophyll contents) of the available genotypes were also examined which revealed the plant anti-xenosis effect that ultimately leads to preference and non-preference which shows remarkable difference in yield within the testing genotypes. Results revealed that maximum yield was recorded in FH-810 (9818.75 Kg/ha) while minimum in FH-1046 (7154.42 Kg/ha). Study revealed that shoot fly and stem borer percentage infestation was negative correlated with plant height, leaf hair density, chlorophyll contents and stem diameter